1999
DOI: 10.1007/s00276-999-0115-9
|View full text |Cite
|
Sign up to set email alerts
|

Martin-Gruber communicating branch: anatomical and histological study

Abstract: We dissected 72 upper limbs of fresh cadavers and found 17 cases with a Martin-Gruber communicating branch (23.6%). These were classified into 4 types: type I (n = 5, 29.4%): communicating branch between the anterior interosseous and ulnar nn, type II (n = 3, 17.6%): Communicating branch between the median and ulnar nn., type III (n = 3, 17.6%): Communicating branch between the muscular branches to the flexor digitorum profundus m., type IV (n = 6, 35.3%): combination of type I or II and type III. At histologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
44
0
7

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 8 publications
5
44
0
7
Order By: Relevance
“…An anomalous connection, commonly known as a MartinGruber anastomosis, may occur between the median and ulnar nerve in the forearm, resulting in varied patterns of innervation to the intrinsic muscles of the hand (14)(15)(16)(17)(18)(19)(20). The MartinGruber anastomosis is median to ulnar in nature (21).…”
Section: Martin-gruber and Marinacci Communicationsmentioning
confidence: 99%
“…An anomalous connection, commonly known as a MartinGruber anastomosis, may occur between the median and ulnar nerve in the forearm, resulting in varied patterns of innervation to the intrinsic muscles of the hand (14)(15)(16)(17)(18)(19)(20). The MartinGruber anastomosis is median to ulnar in nature (21).…”
Section: Martin-gruber and Marinacci Communicationsmentioning
confidence: 99%
“…The mechanism of this partial thenar muscle preservation would be that the anastomotic nerve fibers that had crossed over from the median nerve to the ulnar nerve in the forearm ran unimpeded to the muscles of the thenar eminence so that their regarding the laterality of the anastomosis. Some studies report its right predominance (Nakashima et al [4]; Shu et al [14], Sarikcioglu et al [16], Felippe et al [20]), whereas some others reported left side dominance (Almeida et al [19]; Lee et al [17]). Kimura et al [7] reported a majority of bilateral cases while Taams [21] and Prates et al [10] did not find any significant differences between both sides as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Чаще анастомоз встречается справа [5,[7][8][9], в 10-40 % случаев он бывает двусторонним [1,6,8]. Учитывая широкую распространенность анастомоза, он рассма-тривается как вариант развития, а не аномалия.…”
Section: анатомия и классификацияunclassified
“…Филогенетически анастомоз может рассматри-ваться как остатки общего вентрального нервного ствола, иннервирующего мышцы-сгибатели, присут-ствующего на ранних стадиях развития [1]. Факт того, что наличие анастомоза филогенетически обусловлено, подтверждают данные исследования Shu et al [9], от-мечавших его широкую распространенность у обезьян.…”
Section: анатомия и классификацияunclassified